Augmentation of IFN-γ by bone marrow derived immune cells in the presence of severe suppression of IFN-γ in gingivae induced by zoledronic acid and denosumab in Hu-BLT mice model of ONJ - Kaur, Kawaljit; Sun, Yujie; Kanayama, Keiichi; Morinaga, Kenzo; Hokugo, Akishige; Nishimura, Ichiro; Jewett, Anahid (Frontiers in Endocrinology, 2023)
Percentages of B cells are much higher in wild type mice whereas the proportions of immune subsets in humans and reconstituted hu-BLT peripheral-blood are similar. Therefore, hu-BLT mice is preferable model to study human disease, in particular, immune-pathologies induced by zoledronic acid (ZOL) and denosumab responsible for osteonecrosis of the Jaw. To determine the effects of zoledronic acid and denosumab on IFN-γ secretion and NK cell-mediated cytotoxicity; peripheral blood, bone marrow, spleen and gingiva were obtained after the injection of ZOL and denosumab in mice. Both agents resulted in a severe suppression of IFN-gamma in the gingiva, whereas they heightened the release of IFN-gamma and NK cell-mediated cytotoxicity by the BM-derived immune cells. ZOL increased the IFN-gamma secretion by the spleen and peripheral blood immune cells, whereas denosumab decreased the release IFN-gamma by these cells significantly. Therefore, ZOL and denosumab may likely suppress IFN-gamma secretion in gingiva through different mechanisms. In addition, to the suppression of IFN-gamma secretion, denosumab mediated effect could in part be due to the decrease in the bone resorptive function of osteoclasts due to the induction of antibody dependent cellular cytotoxicity and lysis of osteoclasts, whereas ZOL is able to mediate cell death of osteoclasts directly. Suppression of IFN-gamma in gingiva is largely responsible for the inhibition of immune cell function, leading to dysregulated osteoblastic and osteoclastic activities. Restoration of IFN-gamma in the local microenvironment may result in establishment of homeostatic balance in the gingiva and prevention of osteonecrosis of jaw.